Genetic Selection Pressure on TLR9 Gene Increases Individual Susceptibility to Systemic Inflammatory Disease: A Case Study of Kano State Population - Yusuf Jibril Habib; Mohammed Sani Jaafaru (Eurasian Journal of Science and Engineering)
Toll-like receptor 9 (TLR9) may recognize and generate an immunological response to DNA double-strand; therefore, its link with experimental and serological lupus symptoms must be investigated. Genetic data on the normal frequencies of the TLR9 (rs187084) polymorphism may make it difficult to choose an adequate sample size for case-control association studies. This study investigated how TLR9 (rs187084) polymorphism is typically distributed among the people living in Kano, Nigerians. TLR9 (rs187084) polymorphism was examined in a sample of 315 individuals using the polylmerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. The mutant allele was more common (67%) and gender-independent. The gradual incidence of changed alleles in both identities suggests the population was chosen to survive tuberculosis (TB) and malaria. Though increased TLR9 expression is protective against infections, it might likewise play a part in the development of inflammatory disorders. The high frequency of TLR9 (rs187084) over-expression in Kano State residents may be the result of genetic adaptation to the state's common infectious and parasitic diseases. This is thought to be the outcome of interactions among genetic factors and the terrain. Systemic lupus erythematosus (SLE) and other autoimmune disorders have been linked to this genetic plasticity. Sample sizes for future case-control studies can be determined using the current data. However, to further understand the link between the TLR9-rs187084 variation and the risk of systemic inflammatory diseases, functional investigations might be undertaken.